University Students’ Academic Motivation Profiles: Relationships With Academic Procrastination and Life Satisfaction - Demir Güdül, Meryem; Can, Gürhan; Ceyhan, Aydoğan Aykut (My University, 2019)
In the self-determination theory different motivation types are defined. A person may have these types of motivation simultaneously at different levels and may display a variety of profiles based on such motivational characteristic. This study aimed to examine university students’ motivation profiles that they exhibit depending on the combinations of academic motivation types defined in self- determination theory and to reveal the relationships between these profiles, academic procrastination and life satisfaction. The sample of the study consists of 1700 university students. The data of the study was collected using “Academic Motivation Scale,” “Need Satisfaction Scale,” “Tuckman Procrastination Scale”, “Life Satisfaction Scale”. For the data analysis, there were used hierarchical and non-hierarchical cluster analysis methods to determine the academic motivation profiles. The cluster analyses’ results of research indicated that 33.8% of the students exhibit high (intrinsic and extrinsic motivation levels are high, amotivation level is low), 44.9% of the students exhibit medium (intrinsic and extrinsic motivation levels are medium, amotivation level is below medium) and 21.3% of the students exhibit low (intrinsic and extrinsic motivation levels are low, amotivation level is high) level of academic motivation profile. Results revealed that the students with high motivation profiles obtained higher levels of life satisfaction, whereas they obtained lower academic procrastination levels. It is understood that the students with high motivation profile obtained higher life satisfaction levels, whereas they obtained lower academic procrastination levels than the ones with low motivation profile. The study indicated that intrinsic and extrinsic motivations’ levels are related to both psychological and academic variables.
Keywords: Academic Motivation; Motivation Profile; Self-determination Theory; Academic Procrastination; Life Satisfaction; Akademik Motivasyon; Motivasyon Profili; Kendi Kendini Belirleme Teorisi; Akademik Erteleme; Yaşam Memnuniyeti